South Africa, Lesotho & Swaziland - Bainbridge, James; Carillet, Jean-Bernard; Corne, Lucy; Murphy, Alan; Phillips, Matt; Richmond, Simon (Lonely Planet guidebooks., 2015)
The only guide to include coverage of Lesotho and Swaziland. South Africa is a growth tourist destination. Includes detailed full-colour maps.